Characterization of the complete chloroplast genome of American ginseng, Panax quinquefolius L. Issue 1 (2nd January 2019) - Wang, Yanfang; Wang, Kangyu
Abstract: American ginseng, Panax quinquefolius L. is one of the most widely used and perennial understory herbal remedies in the world, belongs to the Araliaceae family. It is native to Canada, Eastern United States, and North America. American ginseng has always been known as ‘green gold’ in North America. In this study, the complete chloroplast genome of P. quinquefolius L. was determined by the BGISEQ-500 Sequencing. The complete chloroplast genome of American ginseng, ( P. quinquefolius L.) was 156, 267 bp in length and displays a typical quadripartite structure of the large (LSC, 86, 124 bp) and small (SSC, 18, 069 bp) single-copy regions, separated by a pair of inverted repeat regions (IRs, 26, 037 bp each). It harbours 133 functional genes, including 89 protein-coding genes, 36 transfer RNA, and 8 ribosomal RNA genes species. The overall nucleotide composition was: 30.6% A, 31.4% T, 19.4% C, and 18.6% G, with a total G + C content of 38.0%. Phylogenetic relationship analysis shows that P. quinquefolius L. closely related to Panax ginseng .